2007
DOI: 10.1111/j.1439-0418.2007.01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale releases of Trichogramma ostriniae to suppress Ostrinia nubilalis in commercially grown processing and fresh market sweet corn

Abstract: We evaluated the egg parasitoid Trichogramma ostriniae (Pang et Chen) (Hym.: Trichogrammatidae) for control of European corn borer [Lep.:Crambidae: Ostrinia nubilalis (Hu¨bner)] in fields of commercial processing sweet corn in New York in 2002 and 2003.We made inoculative releases of 75 000 T. ostriniae/ha when corn was at midwhorl and regional O. nubilalis activity had begun. Each release field was paired with a similar non-release control. The incidence of egg mass parasitism, number of stalk tunnels, incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In most cases, however, recent trials of Trichogramma augmentation in agricultural crops, whether used inundatively (Andow et al 1995, Glenn and Hoffmann 1997, Scholz et al 1998, Mills et al 2000, Suh et al 2000a, Hommay et al 2002, Lundgren et al 2002 or as a seasonal inoculation (Wang et al 1988, Hoffmann et al 2002, Gardner et al 2007, have not provided sufficient control as a stand alone treatment. While targeting the egg stage is often an effective strategy for preventing crop damage (Hassan 1993), for some pests increased egg mortality can result in reduced larval mortality with the result that there is no reduction in crop damage (Van Hamburg and Hassell 1984).…”
Section: Trichogrammamentioning
confidence: 95%
“…In most cases, however, recent trials of Trichogramma augmentation in agricultural crops, whether used inundatively (Andow et al 1995, Glenn and Hoffmann 1997, Scholz et al 1998, Mills et al 2000, Suh et al 2000a, Hommay et al 2002, Lundgren et al 2002 or as a seasonal inoculation (Wang et al 1988, Hoffmann et al 2002, Gardner et al 2007, have not provided sufficient control as a stand alone treatment. While targeting the egg stage is often an effective strategy for preventing crop damage (Hassan 1993), for some pests increased egg mortality can result in reduced larval mortality with the result that there is no reduction in crop damage (Van Hamburg and Hassell 1984).…”
Section: Trichogrammamentioning
confidence: 95%
“…Studies have shown that the inoculative release (75,000 female wasps per hectare, at whorl stage) of Trichogramma ostriniae Pang and Chen resulted >40% parasitism per generation of O. nubilalis Pang egg masses, significantly higher than control plots in field corn and sweet corn fields (Gardner et al, 2007;Hoffman et al, 2006;Wright et al, 2001Wright et al, , 2002, and increased total generational mortality significantly . These studies suggested, although inoculative releases of T. ostriniae effectively suppress O. nubilalis infestation, refinement in timing, rate of release and frequency of release could enhance the benefits of using these parasitoids inoculatively.…”
Section: Parasitism Of H Zea Eggsmentioning
confidence: 98%
“…(Hymenoptera. Trichogrammatidae), are used for the inundative control of O. nubilalis in Switzerland (Bigler, 1986) and Ostrinia furnacalis (Lepidoptera: Crambidae) in China (see section 5.4.3), but this strategy has not been cost-effective in the USA (Andow et al, 1995;Gardner et al, 2007). To control D. v. virgifera, entomopathogenic nematodes have been tested with mixed results (Munson and Helms, 1970;Wright et al, 1993;Ellsbury et al, 1996;Jackson, 1996).…”
Section: Biological Controlmentioning
confidence: 99%